Attenuated replication and pathogenicity of SARS-CoV-2 B.1.1.529 Omicron - Shuai, Huiping; Chan, Jasper Fuk-Woo; Hu, Bingjie; Chai, Yue; Yuen, Terrence Tsz-Tai; Yin, Feifei; Huang, Xiner; Yoon, Chaemin; Hu, Jing-Chu; Liu, Huan; Shi, Jialu; Liu, Yuanchen; et al. (Nature (London), 2022)
The Omicron (B.1.1.529) variant of SARS-CoV-2 emerged in November 2021 and is rapidly spreading among the human population 1 . Although recent reports reveal that the Omicron variant robustly escapes vaccine-associated and therapeutic neutralization antibodies 2 – 10 , the pathogenicity of the virus remains unknown. Here we show that the replication of Omicron is substantially attenuated in human Calu3 and Caco2 cells. Further mechanistic investigations reveal that Omicron is inefficient in its use of transmembrane serine protease 2 (TMPRSS2) compared with wild-type SARS-CoV-2 (HKU-001a) and previous variants, which may explain its reduced replication in Calu3 and Caco2 cells. The replication of Omicron is markedly attenuated in both the upper and lower respiratory tracts of infected K18-hACE2 mice compared with that of the wild-type strain and Delta (B.1.617.2) variant, resulting in its substantially ameliorated lung pathology. Compared with wild-type SARS-CoV-2 and the Alpha (B.1.1.7), Beta (1.351) and Delta variants, infection by Omicron causes the lowest reduction in body weight and the lowest mortality rate. Overall, our study demonstrates that the replication and pathogenicity of the Omicron variant of SARS-CoV-2 in mice is attenuated compared with the wild-type strain and other variants. The replication and pathogenicity of the Omicron variant of SARS-CoV-2 is attenuated compared with the original strain and other variants.